The influence of IQ, emotional and spiritual perceptions on sports participation in an effort to improve physical health - Gemaini, Andri; Kiram, Yanuar; Komaini , Anton; Eken, Özgür; Jalius, Hardzikrillah; Sepdanius, Endang; Rifki, Muhamad Sazeli; Ayubi, Novadri (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to determine the influence of intellectual intelligence (IQ), emotional, and spiritual perceptions on sports participation to improve physical health. It employed a quantitative research design using a survey method, with questionnaires distributed to participants. A total of 100 respondents, comprising both men and women who were government employees, took part in the study. Data collection was carried out through questionnaires distributed via Google Forms and documentation. Data analysis was conducted using the Partial Least Squares (PLS) method with SmartPLS software version 3. The results of this study indicated that emotions had a positive and statistically significant effect on IQ (p < 0.05), a negative and statistically insignificant effect on perceptions of physical health (p > 0.05), and a positive and statistically significant effect on spirituality (p < 0.05). IQ had a negative and statistically insignificant effect on perceived physical health (p > 0.05). In contrast, spirituality had a positive and statistically significant effect on perceptions of physical health (p < 0.05). This study suggested that for sports participants aiming to enhance their health through physical activity, it was beneficial to incorporate emotional intelligence, IQ, and spirituality. Consequently, the selection of sports activities should consider these factors (emotions, IQ, and spirituality) to maximize their positive effects.